Typification of plant names belonging to subfamily Apioideae (Apiaceae) for the Flora of Argentina - Calviño, Carolina Isabel; Martínez, Susana Graciela (Phytotaxa, 2018)
Names of Apiaceae subfamily Apioideae were found to need typification, as part of the studies for the Flora of Argentina project. To resolve typifications, protologues and type specimens of all names were studied. As a result, 27 lectotypifications (including two second step lectotypifications) and 2 epitypifications are designated here, giving brief justifications for each selection. In addition, a new synonym in Daucus is proposed.